Circulation Timescales and Pathways of Atlantic Water in the Canada Basin: Insights From Transient Tracers ¹²⁹I and ²³⁶U - Payne, Annabel; id_orcid:0 000-0001-9523-0316; Wefing, Anne-Marie; id_orcid:0 000-0001-6855-6062; Christl, Marcus; id_orcid:0 000-0002-3131-6652; Vockenhuber, Christof; Williams, William; Smith, John N.; Casacuberta, Núria; id_orcid:0 000-0001-7316-1655 (Wiley, 2024)
Anthropogenic radionuclides 129I and 236U are used to investigate pathways of the Atlantic Water flow in the Canada Basin, estimate transport timescales, and investigate mixing dynamics within the Atlantic Water layer and the overlying Pacific Water. Transit Time Distribution (TTD) model mean ages indicate water takes 25–35 years to reach the Canada Basin from the entrance of the Arctic, with limited lateral and vertical mixing along the core of the Arctic Ocean Boundary Current. Mode ages obtained from the model yield shorter transport times of 20–32 years. These age estimates agree with previous studies using these radionuclides and ventilation tracers in this region, indicating a steady-state flow of Atlantic Water for the last 15 years. The distribution of the isotopes in the Atlantic layer indicates two pathways Atlantic Water may take into the basin, supported by the distribution of ages in the TTD model. End-member mixing models indicate that the Pacific Winter water acquires a 20%–40% Atlantic Water signal of the radionuclides, upwelled over short periods, most likely along the shelf and Barrow Canyon region. ISSN:0148-0227 ISSN:2169-9275